Formação, gestão e inclusão : a experiência da educação física no município de Viana - Peterle, Ludmila Lima (2017)
This study deals with the issue of continuing education of teachers managing the areas of Physical Education and Special Education in the city of Viana-ES and their actions and policies to favor the inclusion of public-targeted students of Special Education in schools. To fulfill this purpose, the study defines the following objectives: a) to understand the particularities, challenges and possibilities posed to the teachers of the area of Physical Education and Special Education of the municipality of Viana on the public inclusion policies, through Their narratives enunciated during the training meetings; b) to analyze the position of Physical Education teachers in the city of Viana on the process of continuous training in the perspective of inclusion, in which they participated, organized by the teachers / managers, in the year 2015, as a result of the action / work plan elaborated by Them as one of the stages of the course. The study is configured as an exploratory quantitative-qualitative research. As documentary material of the research, the following documents were used: action plan, questionnaires and the narratives of the three teachers / managers related to the municipality of Viana who participated in the Operational Training Group (GOF), in the training course entitled " Teachers/managers of Physical Education for Inclusive Education ", held in 2014, in the Laboratory of Adapted Physical Education, Center for Physical Education and Sports, Federal University of Espírito Santo (Laefa/Cefd/Ufes). As a result of the data analysis concerning the teachers' narratives, by recurrence and relevance we identified a single category/axis of discussion: the continuing education of Physical Education teachers, in the perspective of inclusion. The analysis of this category / axis points to the identification of the absence of continuous training for Physical Education teachers, from the perspective of inclusion, and the initiative of the teachers / managers to elaborate and put into practice in the year 2015 a plan of action/work To fill this gap in training policy in the municipality of Viana. As a result of the data analysis of the questionnaires, it shows that most teachers recognize the importance of continuing education, but they characterize it as a space/place where they meet to exchange experiences and receive information. They identify the training sessions as positive moments of critical reflection on the know-how of the teaching experience. And they highlight aspects such as: the binomial knowledge/training, human and material resources, collaborative work and compliance with laws assist in the process of inclusion of students with disabilities in Physical Education classes.